Pengaruh Variabel Keuangan terhadap Return Awal dan Return 15 Hari Setelah IPO serta Moderasi Besaran Perusahaan terhadap Hubungan antara Variabel Keuangan dengan Return Awal dan Return 15 Hari Setelah IPO di Bursa Efek Jakarta - MISNEN ARDIANSYAH (The Indonesian Journal of Accounting Research, 2013)
This research is aimed to examine the influence of financial variables in the prospectus on initial return and after 15 days return after IPO using non-financial variable as the controlling variable. Another purpose for this research is to examine if the size of company plays as moderating variable on the relationship between financial variables (rate of return on total asset, financial leverage, earnings per share, offer size, profit growth, and current ratio) and initial return and that between financial variables and 15 days return after IPO.The sample for this research are 64 companies listed in Jakarta Stock Exchange from 1995-2000 as the sample for this research.  Data were collected by means of purposive sampling. The analytical methods used are those of multiple regression and absolute-different value regression.The result of the regression analysis for the influence of financial variables on initial return shows that earnings per share significantly influences initial return, whereas rate of return on total asset (ROA), financial leverage, offer size (proceed), profit growth, current ratio, and the size of company do not significantly influence initial return.The result of the regression analysis for the influence of financial variables on 15 days return after IPO shows that financial leverage and earning per-share significantly influences 15 days return after IPO. Whereas rate of return on total asset (ROA), offer size (proceed), profit growth, current ratio, and the size of company do not significantly influence 15 days return after IPO.Also shown from the result, when non-financial variables are used as controlling variables, economics condition significantly influences both initial return and 15 days return after IPO. Where as the age of company, underwriter reputation, auditor reputation and type of industry do not cause any significant influences.The research fails to prove that the size of company plays as a moderating variable on the relationship between financial variables and initial return as well as after 15 days return after IPO.